2007
DOI: 10.1097/01.iae.0000258270.98012.62
|View full text |Cite
|
Sign up to set email alerts
|

Triamcinolone Acetonide Remaining on the Fovea After Successful Macular Hole Closure

Abstract: A 50-year-old highly myopic Asian man had loss of vision in the left eye for 4 months. Visual acuity was 20/30 in the right eye and 20/40 in the left eye. Funduscopy disclosed a tilted disk, a large oval depression located in the region of the myopic conus ( Fig. 1), and a contiguous, transparent elevation of the macula in the left eye. No myopic staphyloma was noted. StratusOCT (Carl Zeiss Meditec, Dublin, CA) scans (Figs. 2 and 3) showed interruption of the hyperreflective band corresponding to the scleral t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…However, we did not find any significant difference in hole closure between the two dyes. Other reports have also shown that residual TA in MHS does not seem to interfere with anatomic or visual improvement [49,50].…”
Section: Discussionmentioning
confidence: 95%
“…However, we did not find any significant difference in hole closure between the two dyes. Other reports have also shown that residual TA in MHS does not seem to interfere with anatomic or visual improvement [49,50].…”
Section: Discussionmentioning
confidence: 95%
“…32,33 There have been anecdotal case reports that have described persistence of TA in the macular hole after vitrectomy surgery but no long-term study has evaluated final outcomes. 34,35 In this article, we report the anatomic and visual outcomes of macular hole surgery with triamcinoloneassisted ILM peeling.…”
mentioning
confidence: 98%
“…For chromovitrectomy, the white steroid may be injected intraoperatively to aid in the observation of the transparent vitreous gel as well as for ILM-peeling in macular hole surgery [2,3]. However, during chromovitrectomy some amount of TA may penetrate through the macular hole, thereby migrating into the subretinal space [22,23]. For retinal drug delivery, subretinal TA-infusion may provide high choroidal drug concentrations for the therapy of angiogenic and edematous chorioretinal diseases [11].…”
Section: Discussionmentioning
confidence: 99%